Special grounds for exemption from criminal liability for crimes in the sphere of economic activity - Akhmetova, A.K.; Rysmagambetova, G.M. (Bulletin of the Karaganda University “Law Series”, 2026)
The aim of the study is to examine and provide a legal analysis of the specific features of the application of special grounds for exemption from criminal liability for crimes committed in the field of economic activity. To achieve this objective, various research methods were employed, including analysis and synthesis, modeling and forecasting, comparative legal and formal-logical methods, as well as a historical approach and other general and specialized methods. The empirical framework of the study is based on the provisions of the criminal legislation of the Republic of Kazakhstan, regulatory resolutions of the Supreme Court and the Constitutional Court of the Republic of Kazakhstan, as well as other regulatory legal acts. The study identifies a number of issues related to legislative gaps, enforcement difficulties, and the ambiguity of legal norms. It proposes revisions in several key areas, including: reparation of damages; the concept of a "first-time offense"; conditions for exemption from criminal liability for specific types of crimes; additional criteria taking into account the personality of the offender and the circumstances of the case; a procedural algorithm for law enforcement agencies and courts; and the conflict between general and special provisions of the Criminal Code of the Republic of Kazakhstan.